GAMBARAN PENANGANAN SAMPAH DI PASAR TERMINAL LAMA KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Djamaluddin G (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2012)
The purpose of this study was to obtain an overview of waste management in the Old Terminal Market Polewali based pewadahan garbage collection point while ( TPS ) , and transportation . This type of research is a descriptive survey research approach to observation , the population in the study are all traders in the Old Polewali Terminal Market , with traders still sample as much as 70 respondents . Sampling with purposive sampling technique . Results of the study note that 70 respondents qualified pewadahan garbage in the Old Terminal Polewali market as much ( 4.3 % ) , while the collection point ( TPS ) and the transport of nothing as much as 100 % qualified . From the research it can be concluded that the picture of waste management in this market is still not eligible . It is recommended to the public including traders with local authorities and institutions concerned in improving the existing waste management system in the market or other public places.